Embryonic development and hatching of Lo%o duvaucelii Orbigny (Loliginidae, Cephalopoda) in the laboratory - Asokan, P K; Kakati, V S (Indian Journal of Fisheries, 2011)
The bulk of the cephalopod production inIndian waters cwnprises cuttlefishes (60%)and the rest consists of squids and a negligiblequantity of octopods (Silas 1986). The biologyand fishery of cephalopods have attractedthe attention of many workers in India (Rao1954, Alagarswami 1966, Silas 1968, 1986,Sarvesan 1969, Silas et al. 1982, Sivalingamand Pillai 1983).